2000
DOI: 10.1128/aem.66.8.3151-3159.2000
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the Pyruvate Dehydrogenase Bypass inSaccharomyces cerevisiae: Role of the Cytosolic Mg2+and Mitochondrial K+Acetaldehyde Dehydrogenases Ald6p and Ald4p in Acetate Formation during Alcoholic Fermentation

Abstract: Acetic acid plays a crucial role in the organoleptic balance of many fermented products. We have investigated the factors controlling the production of acetate by Saccharomyces cerevisiae during alcoholic fermentation by metabolic engineering of the enzymatic steps involved in its formation and its utilization. The impact of reduced pyruvate decarboxylase (PDC), limited acetaldehyde dehydrogenase (ACDH), or increased acetoacetyl coenzyme A synthetase (ACS) levels in a strain derived from a wine yeast strain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
126
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 50 publications
13
126
1
2
Order By: Relevance
“…This finding contrasts with studies on ALD6, which have shown that the growth rate of ald6D strains was significantly less than that of the parental strain on glucose (Meaden et al, 1997;Navarro-Aviñ o et al, 1999). The phenotype might be strain-dependent, however, as other reports concur with our findings (Wang et al, 1998;Remize et al, 2000).…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…This finding contrasts with studies on ALD6, which have shown that the growth rate of ald6D strains was significantly less than that of the parental strain on glucose (Meaden et al, 1997;Navarro-Aviñ o et al, 1999). The phenotype might be strain-dependent, however, as other reports concur with our findings (Wang et al, 1998;Remize et al, 2000).…”
Section: Resultscontrasting
confidence: 81%
“…As the ALD4 and ALD6 genes have been shown to have a role in the oxidation of acetaldehyde to acetic acid (Meaden et al, 1997;Wang et al, 1998;Remize et al, 2000), these were chosen as primary targets for modification. Deletion of the ALD4 gene had no obvious effect on the biosynthesis of acetic acid in GPD2-OP cells when grown anaerobically (unpublished results).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in cells growing in ethanol, further addition of ethanol or acetaldehyde induces an increase in the mRNA steady-state levels only for ALD6, while the mitochondrial counterpart (ALD4 ) does not show a significant modification in its expression. This is consistent with the ability of cytosolic ALDH to partially compensate mitochondrial ALDH absence when its activity is sufficient (Boubekeur et al, 1999(Boubekeur et al, , 2001Remize et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…Traditionally, cytosolic enzymes have been considered responsible for the formation of acetate from glucose while the main role of mitochondrial enzymes would take place during growth on ethanol (Wang et al, 1998;Saigal et al, 1991). However, growth behaviour analysis of mutants in genes encoding aldehyde dehydrogenases have indicated that mitochondrial and cytosolic enzymes may -at least partially and under several conditions -compensate each other (Boubekeur et al, 1999(Boubekeur et al, , 2001Remize et al, 2000).…”
Section: Introductionmentioning
confidence: 99%